2019
DOI: 10.3892/mco.2019.1809
|View full text |Cite
|
Sign up to set email alerts
|

Oncoxin nutritional supplement in the management of chemotherapy- and/or radiotherapy-associated oral mucositis

Abstract: Oral mucositis (OM) is a common and potentially dangerous complication of anticancer treatment. Since there are only few therapeutic options for OM, there is a need to identify novel approaches to its management and prevention. The aim of the present study was to evaluate the efficacy of Oncoxin (ONCX), a nutritional supplement that contains microelements, vitamins, amino acids and certain biologically active substances of natural origin, in cancer patients who receive chemotherapy, radiotherapy or a combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 12 publications
1
24
0
3
Order By: Relevance
“…Moreover, by the end of three weeks, the level of albumin was higher in the OOS cohort and liver toxicity was lower in that cohort. Benefits of OOS in patients treated with chemotherapy or radiotherapy were also observed by Shumsky et al [76], who studied the impact of OOS on oral mucositis in 15 patients, 10 treated with OOS and five control. Using the World Health Organization Oral Toxicity Scale, the authors reported a 41% decrease in oral mucositis in the OOS-treated group as compared to minimal change in the control group, which was allowed to use other types of care for oral mucositis.…”
Section: Clinical Activity Of Oossupporting
confidence: 62%
“…Moreover, by the end of three weeks, the level of albumin was higher in the OOS cohort and liver toxicity was lower in that cohort. Benefits of OOS in patients treated with chemotherapy or radiotherapy were also observed by Shumsky et al [76], who studied the impact of OOS on oral mucositis in 15 patients, 10 treated with OOS and five control. Using the World Health Organization Oral Toxicity Scale, the authors reported a 41% decrease in oral mucositis in the OOS-treated group as compared to minimal change in the control group, which was allowed to use other types of care for oral mucositis.…”
Section: Clinical Activity Of Oossupporting
confidence: 62%
“…Oncoxin is a solution containing amino acids, vitamins, micronutrients and biologically active substances. Previous studies showed that ONCX was able to increase life expectancy, improve QoL and appetite in patients with end-stage hepatocellular carcinoma (10) and effectively reduce the severity of oral mucositis symptoms in patients receiving CT, radiation therapy or their combination (11).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Ocoxin abrogated hepatic-toxicity related ALT and AST enzyme increase in 92% of the patients under adjuvant CT regiment after 3 weeks of treatments, while only the AST and ALT levels of 50% of the patients from non-supplemented group remained unchanged. This reduced hepatic toxicity was further confirmed by Shumsky et al (2019) in patients receiving Ocoxin to mitigate CT and RT related oral mucositis [55]. They reported 4 and 7-fold reduced ALT and AST levels in patients under Ocoxin supplementation compared to those receiving CT and RT.…”
Section: Evidences Of the Positive Effect Of Ocoxin In The Liver Metamentioning
confidence: 85%
“…This damage is partly mediated by inflammatory mediators such as IL-1β, TNF-α and inducible nitric oxidase sinthase (iNOS) 53 , 54 . Interestingly, Ocoxin exerts a curative effect in patients suffering from this side effect, diminishing the ulcerative area and facilitating the healing of the affected tissue 55 , therefore eliminating the pain related to eating and drinking. This effect may be due to the anti-inflammatory properties of Ocoxin, which confers the ability to inhibit TNF-α upregulation, as reported in other pathologies 25 .…”
Section: Ocoxin Improves Ct and Rt Related Toxicitymentioning
confidence: 99%